Electrically‐Driven Oxygen Vacancy Aggregation and Displacement in YBa2Cu3O7−δ Films. (7th April 2022) - Collienne, Simon; Marinković, Stefan; Fernández‐Rodríguez, Alejandro; Mestres, Narcís; Palau, Anna; Silhanek, Alejandro V.
Abstract: Combining direct visualization of current‐induced oxygen migration through optical microscopy and finite element modeling of driven oxygen diffusion, it is possible to estimate the average activation energy of oxygen motion in the crystallographic ab ‐plane of c ‐axis oriented polycrystalline YBa2 Cu3 O7−δ films. Experiments and modeling are compared side‐by‐side for the case of constant current electromigration as well as for a train of current pulses of varying amplitude. The simulations reproduce the induced resistance changes after electromigration and confirm a high degree of spatial inhomogeneity in the stoichiometry. Assuming a temperature and oxygen concentration dependent resistivity, the authors are able to capture the change of superconducting critical temperature, normal state resistance, and the development of multistep transitions as a function of the electromigration history. The simulations are further applied to scrutinize the influence of activation energy, disorder in oxygen content, and initial oxygen concentration on the electromigration process. These results shed new light on the non‐local modifications produced by the electromigration process on oxide conductors. Abstract : Oxygen content is the key ingredient in copper oxides allowing to access a variety of electronic phases spanning from antiferromagnetic semiconducting, non‐Fermi liquid to superconducting behavior. In this report, the lateral diffusion of oxygen vacancies in YBaCuO under electrical stress is mapped and linked to electro‐thermal landscape predicted by quantitative finite element simulations.